2007
DOI: 10.1161/hypertensionaha.107.088534
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Escape by the Kidney But Not the Heart in Experimental Asymptomatic Left Ventricular Dysfunction

Abstract: Abstract-Unlike healthy subjects, overt congestive heart failure cannot "escape" the sodium-and water-retaining actions of mineralocorticoid excess. It is undefined whether escape occurs in asymptomatic left ventricular dysfunction (ALVD), which is characterized by preserved sodium homeostasis, natriuretic peptide activation, and normal circulating aldosterone. We hypothesized that, in ALVD, mineralocorticoid excess with exogenous deoxycorticosterone acetate (DOCA) would overwhelm renal compensatory mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
2
4
0
2
Order By: Relevance
“…Further studies are needed to investigate possible early activation of aldosterone. The activation of aldosterone at 16 wk without marked sodium and water retention is consistent with the phenomenon of mineralocorticoid escape (3,8). Specifically, the kidney escaped from the sodium-retaining properties of aldosterone excess, as we previously demonstrated in a canine model of mild LV dysfunction (8).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Further studies are needed to investigate possible early activation of aldosterone. The activation of aldosterone at 16 wk without marked sodium and water retention is consistent with the phenomenon of mineralocorticoid escape (3,8). Specifically, the kidney escaped from the sodium-retaining properties of aldosterone excess, as we previously demonstrated in a canine model of mild LV dysfunction (8).…”
Section: Discussionsupporting
confidence: 82%
“…The activation of aldosterone at 16 wk without marked sodium and water retention is consistent with the phenomenon of mineralocorticoid escape (3,8). Specifically, the kidney escaped from the sodium-retaining properties of aldosterone excess, as we previously demonstrated in a canine model of mild LV dysfunction (8). Relevant to this pathological role of aldosterone in this model of mild CKD is the study by Edwards et al (12) that have recently demonstrated using magnetic resonance imaging that spironolactone, in patients with early mild CKD, resulted in a reduced LVH in association with a reduction in proteinuria.…”
Section: Discussionsupporting
confidence: 63%
“…We previously demonstrated cardiac fibrosis with exogenous mineralocorticoid excess alone in experimental systolic dysfunction34 and increased fibrosis and diastolic dysfunction in renal wrapping induced hypertension35; although DOCA also increased BP in the renal hypertension model. Here we confirm and extend these findings in pressure overload induced produced by TAC, independent of further BP elevation or increased salt intake/nephrectomy and provide insight into the mechanism whereby pressure overload hypertrophy sensitizes the heart to mineralocorticoids.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, contrary to current practice guideline recommendations, dietary sodium restriction may be detrimental particularly in early stage HF and contribute to the premature acceleration of PRA and excess aldosterone activation, and a more moderate sodium diet may aid in delaying the neurohormonal progression of early HF. It should be noted that in the study by Costello‐Boerrigter et al , in a canine model of early asymptomatic LV dysfunction, exogenous administration of the mineralocorticoid DOCA (deoxycorticosterone acetate) to mimic aldosterone failed to induce sodium retention but did induce early cardiac fibrosis. While findings are variable in the reported literature and our data do not support a recommendation for a specific desirable dietary sodium cut‐off point in humans, the current study supports the conclusion that careful assessment of dietary sodium in the setting of HF merits further prospective investigation, particularly in patients with Stage B and compensated Stage C HF receiving optimal medical therapy.…”
Section: Discussionmentioning
confidence: 99%